2008
DOI: 10.1177/0164027508319655
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neighborhood and Individual Change on the Personal Outcomes of Recent Movers to Low-Income Senior Housing

Abstract: The objective of this study was to determine the effects of neighborhood and individual change on the personal outcomes of recent movers to Canadian government-subsidized senior citizen apartment buildings (SCAs). The authors' sample included 137 recent movers to 25 SCA projects in Winnipeg, Manitoba, who participated in a longitudinal survey. The analysis involved testing four logistic and ordinary least squares regression models, with personal state outcomes of the moves (self-rated health, morale, depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Most common disciplinary affiliations were thus with psychology, occupational therapy and economics. Two-thirds of the studies (n = 57) were either signed by one author (n = 30) [ 29 , 40 , 46 , 49 , 59 , 62 65 , 68 – 70 , 72 , 74 , 76 , 80 , 93 95 , 97 , 100 – 108 , 110 ], by co-authors in the same discipline (n = 18) [ 10 , 41 45 , 52 , 54 , 55 , 67 , 73 , 75 , 83 85 , 90 , 96 , 99 ], or by co-authors in the same research domains (n = 9) [ 33 , 47 , 48 , 51 , 57 , 58 , 77 , 87 , 98 ]. Among the remaining 29 studies (34%), 21 were co-signed by authors from two different research domains [ 21 – 25 , 28 , 30 , 34 , 36 , 39 , 50 , 53 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most common disciplinary affiliations were thus with psychology, occupational therapy and economics. Two-thirds of the studies (n = 57) were either signed by one author (n = 30) [ 29 , 40 , 46 , 49 , 59 , 62 65 , 68 – 70 , 72 , 74 , 76 , 80 , 93 95 , 97 , 100 – 108 , 110 ], by co-authors in the same discipline (n = 18) [ 10 , 41 45 , 52 , 54 , 55 , 67 , 73 , 75 , 83 85 , 90 , 96 , 99 ], or by co-authors in the same research domains (n = 9) [ 33 , 47 , 48 , 51 , 57 , 58 , 77 , 87 , 98 ]. Among the remaining 29 studies (34%), 21 were co-signed by authors from two different research domains [ 21 – 25 , 28 , 30 , 34 , 36 , 39 , 50 , 53 ,…”
Section: Resultsmentioning
confidence: 99%
“…More than half of the studies (n = 47) looked at the housing decisions of older adults only after they had made a choice [ 10 , 26 , 27 , 31 35 , 37 , 39 , 41 49 , 56 , 58 , 59 , 62 , 63 , 65 67 , 70 , 71 , 73 – 75 , 78 , 80 , 82 , 85 87 , 91 , 92 , 96 , 99 , 102 – 104 , 107 – 109 ]. Four more examined only during the decision process [ 51 , 60 , 64 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the numbers of older persons waiting for rental assistance in the U.S., this population is nearly invisible. Studies in Australia, Canada, and Europe report that older persons apply for publicly subsidized housing because they have health problems and lack informal supports and because public housing provides access to shops and public transportation (Burke, Neske, & Ralston, 2005;Prescott-Clarke, Clemons, & Park, 1994;Smith & Sylvestre, 2008;van Bilsen, Hamers, Groot, & Spreeuwenberg, 2006). One U.S. study of nonelderly, nondisabled applicants reported homelessness, rent burden and poor housing quality among waitlisted persons (Leopold, 2012).…”
Section: Forty-five Percent Of Tenants In Privately-owned Hud-subsidimentioning
confidence: 99%